(3YbO GdLeGf aj JGQjN Cgd GdReGfs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s ((3eMeO Hf eMeO Hf eMeO GdYQGbi s)
(3ChdgG (B:s
(3GdfhY GdKGfi YTQ ai UaI YjSi Ydjg GdSdGe s
(3eLdO Hg KeGf bWY eJaQbI ef GdcJGH cGf hLOgG GdMGL eUWai QFjS GdcJGH ai SfI (B1061(3g` eSQhbI ef ecJHI GdSdWGf CMeO GdKGdKs
(3Ke CYOgG Edi GdecJHI GdePchQgs
(3hbOe dgG fHPI JPcQ ajgG bUI JQLeI cJGH YbO GdLeGf ddYjfi Edi GdJQcjI hGdfSN GdJi GYJeO YdjgG ai Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs